Estimating effects of arable land-use intensity on farmland birds using joint species modelling - Stjernman, Martin; Olsson, Ola; Smith, Henrik G.; Sahlin, Ullrika (Lund University, 2019)
This study seeks evidence of benefits to farmland birds of reversing land use intensification on and among arable fields and to what extent benefits are moderated by presence of more natural habitats (semi-natural pastures and field borders). The study compares bird numbers for a set of farmland bird species in landscapes/sites differing in agricultural land use and amount of semi-natural habitats. The dataset is comprised of bird counts and agricultural habitat characteristics from a set of 1km radius circular landscapes distributed in the most to medium productive regions in Scania (southern-most province of Sweden). Study sites (landscapes) where selected to maximise orthogonality in the habitat characteristics. Bird counts in each landscape where made for 5 min. at 11 – 16 points distributed in a 4 by 4 grid (approx. 400 m between points; half the points, “columns” 1 and 3, where moved to nearest field border; points more than 50 m outside farmland where discarded; points that could not be accessed (gardens etc.) where moved to nearest access point). Landscapes were visited twice (>= 1 week in between) during the period 2011-05-11 – 2011-06-14. Only counts of a set of farmland birds is included in the dataset (see metadata). All birds seen or heard within 150 m were counted. Habitat characteristics were extracted from the IACS database (Blockdatabasen) maintained by the Swedish Board of Agriculture for administration of subsidies. Full description of design and methods can be found in Stjernman et al. Ecological Applications 2019 (In press).

The paper (Stjernman et al Ecological Applications 2019, currently In Press) and dataset are to be cited when using the dataset.

I den här studien undersöker vi förhållandet mellan fågelförekomst och intensitet i markanvändning i ett antal landskap (1km radie) belägna i Skånes slätt- och mellanbygd. I upp till 16 punkter (ca 400 m emellan varje) räknades vid två tillfällen alla fåglar tillhörande ett urval arter som betraktas beroende av jordbruksmark. Alla individer inom 150 m från observationspunkten sedda inom 5 min inkluderades. Markanvändningsinformation för landskapen hämtades från Jordbruksverkets Blockdatabas. Utförligare information om variabler i data finns i metadata och vidare finns metoder och data utförligare beskrivna i Stjernman et al. Ecological Applications (In press).

Artikeln (Stjernman et al Ecological Applications 2019, In Press) och dataset citeras vid användning av data.
Skattning av effekter av jordbrukets markanvändning på jordbruksfåglar med hjälp av "joint species modelling"
Keywords: BIOLOGY; BIOLOGI; Biodiversity; Biologisk mångfald; ANIMAL ECOLOGY AND BEHAVIOR; LANDSCAPE ECOLOGY; LANDSCAPE MANAGEMENT; AGRICULTURAL LANDS; BIOLOGICAL RECORDS; Environment and conservation; Miljö och naturvård; Plants and animals; Växter och djur; Ecology; Ekologi; Agricultural Science; Jordbruksvetenskap; Biota; Biologi och ekologi